Quantifying movement of the coffee berry borer at the interface between coffee plantations and adjacent land uses - Vilchez-Mendoza, Sergio J.; Ronin, Antoine; Bommel, Pierre; Cilas, Christian; Bagny Beilhe, Leila (Frontiers in Sustainable Food Systems, 2024)
Insect pests cause important crop production losses worldwide. Their distribution and movement are affected by climate and land use change and agriculture intensification. Site colonization by insect pests is dependent on pest dispersal capability, the availability of resources, the presence of competitors or predators, the weather conditions and the characteristics of the surrounding landscape. Movement of pests between the plots might be considered in pest management strategies to counterbalance the traditional plot oriented strategies. In this study, our objective was to provide evidence of the movement of the coffee berry borer (CBB), the most important pest in coffee cultivation, from neighboring coffee plantations to adjacent land uses at different time periods of the coffee production cycle. For 10 months we captured the CBB with funnel traps in 13 coffee plots that had an interface with forests, pastures, and abandoned coffee plantations in Costa Rica. At each interface, we established three transects with a minimum distance of 50 m between them, in the direction of the wind. Within each transect, we placed four traps 20 m apart. We fitted generalized linear mixed models to evaluate the relationship between CBB captures and the type of interface, the position of the trap, wind velocity, rainfall, temperature and relative humidity, and their interactions. Our findings suggest that CBB moves into adjacent land uses when the coffee resource in the plot is limited. This effect varies according to the interface and the position of the trap. We also found an interaction between the interface and the position of the trap with the wind and relative humidity. Our findings suggest that movement of the CBB partly depends upon the adjacent land uses. The forest creates a barrier to CBB movement and may prevent the transport of the CBB considering the action of the wind speed. The pasture may facilitate movement of the CBB through the action of the wind speed and infest coffee plantations beyond its dispersal capacity. Our results support the importance of considering the landscape context when developing CBB management strategies.